PEOPLE ROLE IN SER VICE DELIVERY : PERAN DOSEN DAN MAHASISWA DALAM PROSES PEMBELAJARAN DI KELAS - Fatik Rahayu (Media Riset Bisnis & Manajemen, 2011)
Educational literatures suggest that there is mounting pressure from customers of higher education to close the gap between their expectation of institutional performance and the actual performance. Therefore, it is imperative that higher educations actively monitor the quality of their service. The overall course evaluation is one of the most significant trends in current higher eduction quality. This research concerns with the impact of instructor' role and student role on the overall course evaluation. A questionnaire was developed with item measures that captures the constructs in the conceptual model. A survey of higher education student was undertaken. The data are analysed with multiple regression. The result showed that the instructor and student play a role in explaining student perceptions of the overall course evaluation.Keywords : The role of instructor, The role of student, The overall course evaluation, Higher education quality